Das Kaninchen vor der Schlange: Europäische Wirtschaftspolitik nach dem Anschlag vom 11. September 2001 - Herr, Hansjörg (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
The terrorattack hit the western world in a situation of a sharp cyclical downturn in the USA, Europe and Japan. Mainly because of increased uncertainty the downturn will be intensified by the attack. Immediately after the attack US monetary and fiscal policy became even more expansive. In Europe monetary policy reacted very reluctantly. Active fiscal policy in the Euro-area is nearly not existing as the Stability and Growth Pact as well as neo-liberal ideology prevents fiscal measures. The inactive economic policy in the Euro-area is not only dangerous for Europe but also a depressing factor for the world economy.